1993
DOI: 10.1021/ja00068a041
|View full text |Cite
|
Sign up to set email alerts
|

Water and the silica surface as studied by variable-temperature high-resolution proton NMR

Abstract: The interaction of water with the silica surface is explored using *H NMR techniques. The silica is examined at various levels of hydration/dehydration and temperature, using line narrowing by magic-angle spinning, with or without multiple-pulse averaging ofdipolar interactions. Water physisorbed on the silica surface exhibits a freezing point depression of roughly 40 K. Molecular reorientation of physisorbed water at rates in the tens of kilohertz range is observed through interference with multiple-pulse lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 0 publications
10
155
0
3
Order By: Relevance
“…As a proof, these protons are characterized by a long T 2 of 17 ms (Table S-1 of the Supporting Information), indicative of very weak dipolar interactions. The assignment of the 1.8-ppm line to isolated silanols is in agreement with previous 1 H NMR studies based on thermal dehydration [60,62] and T 2 relaxation-time measurements. [60,63] The resonance at 2.8 ppm, which exhibits a short T 2 (2.4 ms) is probably due to weakly hydrogen-bonded silanols.…”
Section: H Mas Nmr Spectroscopy Of Dried Glassessupporting
confidence: 91%
See 1 more Smart Citation
“…As a proof, these protons are characterized by a long T 2 of 17 ms (Table S-1 of the Supporting Information), indicative of very weak dipolar interactions. The assignment of the 1.8-ppm line to isolated silanols is in agreement with previous 1 H NMR studies based on thermal dehydration [60,62] and T 2 relaxation-time measurements. [60,63] The resonance at 2.8 ppm, which exhibits a short T 2 (2.4 ms) is probably due to weakly hydrogen-bonded silanols.…”
Section: H Mas Nmr Spectroscopy Of Dried Glassessupporting
confidence: 91%
“…[63][64][65][66] The assignments of various peaks of water, isolated and/or bound silanols in the 1 H NMR spectra have been elucidated [60][61][62][63][64] despite lines broadening arising from strong 1 H-1 H dipolar couplings and/or chemicalshift anisotropies. As shown in previous studies, [60,63] measurements of the spin-spin T 2 relaxation time allow the confirmation of the attributions of the various protons. Indeed, the spin-spin magnetization echo decay is dependent on the dipolar dephasing, which decreases in the presence of strongly homonuclear coupled protons, meaning that long T 2 times are due to weakly coupled protons.…”
Section: H Mas Nmr Spectroscopy Of Dried Glassesmentioning
confidence: 99%
“…Several investigators have shown that the surface facets of b-crystoballite are a good model for silica. 23,24,25,26,27,28,29,30,31 The most stable facet of b-crystoballite is the (111) surface, which is made up rings containing six Si atoms. Every other Si atom on the (111) surface of b-crystoballite is terminated by an OH group.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The study of the water vapor uptake by dehydrated silica reaching the Earth's surface by scattering the incoming radi-has a long history (8,9,(14)(15)(16)(17)(18)(19). Usually silica has been ation (2).…”
Section: Introductionmentioning
confidence: 99%